Impending paradoxical embolism - Henmi, Soichiro; Nakai, Hidekazu; Yamanaka, Katsuhiro; Omura, Atsushi; Inoue, Takeshi; Okada, Kenji (Journal of cardiology cases, 2021)
An impending paradoxical embolism (IPDE) is seldom observed in clinical practice. We report a case of IPDE in a 67-year-old female with severe dyspnea and hypotension, which was detected and successfully treated with emergent cardiac surgery. The optimal treatment is still controversial. We believe that emergent surgery always should be considered in patients with IPDE. <Learning objective: We report a rare case of an impending paradoxical embolism in a 67-year-old female with severe dyspnea, which was successfully treated with emergent cardiac surgery. An emergent open surgery always should be considered in patients with impending paradoxical embolism.>